OPTIMIZATION AND EFFICIENCY ANALYSIS OF DFT HYDROPONIC SYSTEM USING 100 WP SOLAR PANEL BASED ON MICROCONTROLLER: OPTIMALISASI DAN ANALISIS EFISIENSI SISTEM HIDROPONIK DFT MENGGUNAKAN PANEL SURYA 100 WP BERBASIS MIKROKONTROLER - Jhaniya Zahra Nawawi; Hadi Nasbey; Haris Suhendar (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
This study aims to optimize and analyze the efficiency of the Deep Flow Technique (DFT) hydroponic system, which has proven effective in plant productivity but remains heavily reliant on stable and affordable electricity. Integrating hydroponic systems with renewable energy sources, such as solar energy, presents a promising solution to this challenge. Solar panels, as one of the most popular renewable energy technologies, have significant potential to support DFT hydroponic systems in a sustainable manner. By utilizing a 100Wp solar panel, the hydroponic system can operate independently and environmentally friendly, especially in regions with high sunlight intensity. A microcontroller, as a key component in automation systems, can efficiently control the operation of the DFT hydroponic system. Through optimization and efficiency analysis, the integration of DFT hydroponic systems with solar panels and microcontroller control offers a more effective and economical solution for enhancing plant productivity.